High‐Performance White Organic Light‐Emitting Diodes with High Efficiency, Low Efficiency Roll‐Off, and Superior Color Stability/Color Rendering Index by Strategic Design of Exciplex Hosts. Issue 23 (10th September 2019) - Ying, Shian; Xiao, Shu; Yao, Jingwen; Sun, Qian; Dai, Yanfeng; Yang, Dezhi; Qiao, Xianfeng; Chen, Jiangshan; Zhu, Tengfei; Ma, Dongge
Abstract: White organic light‐emitting diodes (WOLEDs) are one of the most cogent candidates for environment friendly and healthy solid‐state lighting due to many unique merits. Here, a strategic design of exciplex hosts is applied to simultaneously realize the superior color stability, high color rendering index (CRI), high efficiency, and low efficiency roll‐off properties of WOLEDs. The resulting WOLEDs emit the forward‐viewing maximum power efficiency (PE) of 59.9 lm W −1, and the PE still remains 45.3 and 31.9 lm W −1 at 1000 and 5000 cd m −2, respectively, exhibiting extremely low efficiency roll‐off. More remarkably, the devices also show high CRI over 80 and extremely stable spectral emission in the luminance ranges from 1000 to 15 000 cd m −2 . The excellent performances indicate the validity of the structure design and provide a new route for the development of high‐performance WOLEDs. Abstract : High‐performance white organic light‐emitting diodes with low efficiency roll‐off, superior color stability, and high color rendering index are achieved by strategic design of exciplex hosts for different color phosphors. The forward‐viewing maximum power efficiency is 59.9 lm W −1, and the values still remain 45.3 and 31.9 lm W −1 at 1000 and 5000 cd m −2, respectively, exhibiting extremely low efficiency roll‐off.